2022
DOI: 10.18280/ts.390542
|View full text |Cite
|
Sign up to set email alerts
|

AIAVRT: 5.0 Transformation in Medical Education with Next Generation AI- 3D Animation and VR Integrated Computer Graphics Imagery

Abstract: Immersive recreations of actual classrooms in virtual reality (VR) provide students and teachers with insights into the classroom. Recent technological advances in haptics, display systems, and motion detection create a realistic and interactive experience, making VR ideal for hands-on training. The main fields of application for VR are interventional procedures like surgeries. VR devices allow teachers to quickly identify and address difficulties in the clever learning for complicated surgery course. With thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Thus, implementing a virtual classroom model that incorporates these elements can create a more accessible, user-friendly, and interactive educational environment. As a result of these insights, the study encourages broader adoption of VR and AI technologies in medical education (Kumar et al, 2022).…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 79%
“…Thus, implementing a virtual classroom model that incorporates these elements can create a more accessible, user-friendly, and interactive educational environment. As a result of these insights, the study encourages broader adoption of VR and AI technologies in medical education (Kumar et al, 2022).…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 79%
“…Kumar et al [20] recommended AI-3D Animation and VR Integrated Computer Graphics Imagery in modern education. This article aims to provide universities with information that will be useful to them as they use a virtual reality (VR) e-learning platform to maintain and improve their education and learning system.…”
Section: Related Studymentioning
confidence: 99%
“…The study found that the learning process, which uses a teaching factory based on project‐based learning and problem‐based learning, effectively develops the entrepreneurial spirit of its graduates. In the field of medical education, work 67 discussed the transformation in medical education with the next generation AI—3D animation and VR integrated computer graphics imagery. The study highlighted the potential of these advanced technologies in enhancing the learning experience in medical education.…”
Section: Societal Impacts Of Animationmentioning
confidence: 99%